Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Sektor Food And Beverage) - Lediana Sufina; Khadafi, Rafito Rachmat (Jurnal Keuangan dan Perbankan, 2025)
Firm value is one of the key indicators in the capital market that reflects stakeholders’ perceptions of a company’s performance and prospects. Changes in firm value can be influenced by various factors that illustrate a company’s ability to achieve business success. This study aims to analyze the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on firm value in manufacturing companies within the Food and Beverage sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The independent variables in this study consist of the Board of Commissioners, Board of Directors, Managerial Ownership, and CSR disclosure, while the dependent variable is firm value measured using the Tobin’s Q ratio. This research employs a quantitative approach using secondary data obtained from companies’ financial statements and sustainability reports. The sample comprises 12 companies with a total of 60 observations. Data analysis was performed using panel data regression with the Common Effect Model (CEM) approach through EViews 12 software. The results indicate that GCG and CSR simultaneously have a significant effect on firm value. Partially, the Board of Commissioners and Board of Directors show a negative effect on firm value, while the Audit Committee has no significant influence. Meanwhile, CSR disclosure has a positive and significant effect on firm value. These findings are consistent with the Signalling Theory, which suggests that CSR disclosure provides a positive signal to investors as it reflects the company’s commitment to social responsibility and business sustainability.